The Impact of Traditional Toys on the Character Value of Creation of Karsa Children, Karanganyar Village, Jepara - Moh. Syaffruddin Kuryanto; Rizal Muhammad Hashemi; Lintang Kironoratri (Journal on Education, 2023)
This study aims to find out how the impact of traditional children’s toys on the value of the creative character of the sense of initiative of children in Karanganyar village, Jepara. In this study, the method used is qualitative, and the research data presented is in the form of narrative data. Data collection techniques in this study were conducted using interviews, observation, recording, and documentation. The data analysis technique in this study is a qualitative analysis developed by Miles and Huberman, which is carried out with the following steps: (a) data reduction (b) data presentation (c) conclusion. The results show that playing with traditional toys has an impact on the value of the creative character of the sense of initiative in Karanganyar children which is characterized by being able to develop aspects of critical or creative thinking, developing aspects of feeling of heart responses from the sense including being able to feel and appreciate, then develop the ability to will. Or real action.